The Power Generated by the Waves - Hemmati, Mohammad Hojjat Poor; Najafi, Mahsa; Hosseini, Seyedeh Ghazal; Ghazvini, Zahra; Jabarnia, Mehdi (European Journal of Applied Sciences, 2024)
Climate change and the emission of many polluting gases spread by fossil fuels have been causing plenty of problems for the environment. The energies provided by natural resources with zero release of greenhouse gases can be proper replacements to sustain the need of the power demand. This survey has investigated sustainable energy sources with the usage of green and clean sources including hydropower such as wave energy, sunlight, and wind power and then converting these natural resources into pure electrical energy. The presented data is brought from the libraries of several papers that have been printed previously. The survey illustrated the results of the following papers and brought innovative concepts to produce electrical energy with environment-friendly solutions. A plate-type wave energy converter has been thoroughly examined as a viable method for utilizing wave energy to transport seawater to desalination sites. The study rigorously investigated the impact of various factors on the converter’s performance and presented groundbreaking concepts for producing electrical energy through environmentally friendly solutions.